High Prevalence Level of Avian Malaria in the Wild Population of the Java Sparrow - Pramana Yuda (Universitas Atma Jaya Yogyakarta, 2009)
Java sparrow (Padda oryzativa) is anendemic bird to Java and Bali. It used to be avery common bird, but due to over exploitationthe bird has declined and been classified asVulnerable (BirdLife International, 2001). InIndonesia bird-keeping is a popular pastime,with deep cultural roots (Jepson and Ladle,2005). It is widely assumed that the hobbynegatively affects wild populations of commonas well as threatened birds (Jepson and Ladle,2005; Nash, 1994), such as Java sparrow.